Guidelines for Skill Development of Private School Administrators under the Office of Education, Phra Nakhon Si Ayutthaya Province - krisin, wasana; Phattharakul, Weeraphat (Mahachula Academic Journal, 2024)
The objectives of this research are to (1) study the current conditions and desired conditions for developing the skills of private school administrators (2) present guidelines for developing the skills of private school administrators. Method operation the research has 2 steps: (1) study the current condition Desired conditions and guidelines for developing the skills of private school administrators. Under the jurisdiction of the Phra Nakhon Si Ayutthaya Provincial Education Office. It is necessary to develop the skills of private school administrators. (2) Present guidelines for developing the skills of private school administrators. There were 7 Key informants, which were obtained by means of purposive sampling. The research instrument used was a semi-structured interview. And analyze content data the results of the research found that: (1) Current conditions and desired conditions for developing the skills of private school administrators. Overall, it is at a high level. (2) Guidelines for developing the skills of private school administrators consist of 4 areas as follows: (1) Technical skills Administrators should allocate budgets and administrative resources to enable teachers and educational personnel to develop the mselves by acquiring additional knowledge related to their work appropriately. (2) human relations skills Management should organize activities and projects to build good relationships with personnel. To create a good atmosphere for working within the organization (3) conceptual skills Executives should organize meetings to clarify for personnel to have a common understanding of the overall picture of the organization. To have the aim of developing the organization in the same direction. (4) educational and teaching skills Administrators should promote education. By allocating sufficient time to teachers and personnel to provide learning for students, including developing the school’s curriculum to keep up with the changing conditions of today’s society.